Missio hominum guided by an understanding of Ubuntu for missio Dei: Nico Smith"s discovery - Thinane, Jonas Sello (HTS teologiese studies, 2021)
Missio hominum as a theological framework within the discipline of missiology in understanding missio Dei still lacks proper exploration. Few attempts have been made by theologians in the past but in different disciplines other than missiology. The exception is the previous studies by Nico Smith who investigated and conceptualised the subject at great length. This article builds on Smith’s perspectives on missio hominum with the aim of providing an in-depth understanding of the subject in an African context. This shall be achieved by juxtaposing missio hominum with an African concept of Ubuntu through a literary analysis. Ubuntu is imperative in understanding the significance of human beings within the Christian mission in fulfilling the purpose of missio Dei . Contribution: This article makes two important contributions in the field of missiology – first, by illustrating through missio hominum that human beings are God’s partners in accomplishing his mission on earth, and second, by illustrating through Ubuntu that human beings should partner with one another for the same purpose.